Advancing the Evidence Base of Future Warming Impacts on Human Mobility in African Drylands. Issue 10 (7th October 2021) - Thalheimer, Lisa; Williams, David S.; van der Geest, Kees; Otto, Friederike E. L.
Abstract: A better understanding of climate change impacts and resulting human responses (climate‐related human mobility) have been identified as a research priority by the climate science community. Here, we provide the basis for future research efforts by identifying knowledge gaps and consolidating published evidence in the IPCC 1.5 Special Report (SR15) with recent evidence from climate science and the literature on human mobility in African drylands, a region where migrants are particularly vulnerable to climate change. We first synthesize climatic changes and their projected impacts across the region to then contextualize the projected impacts with current knowledge regarding the effect of anthropogenic climate change on human mobility. We discuss these often indirect impact channels and argue that a systems approach is needed to address the interconnectedness of climate impacts and the cascading risks of adverse consequences for human mobility. Plain Language Summary: The Paris Agreement recognizes that climate change and extreme weather events alter human mobility patterns. Even under an optimistic scenario, an increase in global temperature of 1.5°C above pre‐industrial levels is likely to increase the numbers of people vulnerable to climatic stress while limiting the capacity for effective climate change adaptation. Under a less optimistic scenario, the disruption is expected to be worse. Yet, the impacts of different warming scenarios, including observed warming, on human mobility remain insufficiently understood and discussed in policymaking. A synthesis of empirical evidence from the IPCC Special Report on Global Warming of 1.5°C and subsequently published literature on climate change effects in African drylands highlight implications of warming scenarios on human mobility in this region, where climatic change is a defining feature of local communities and predominantly agricultural economies. Adverse effects of climate change on African dryland communities may not necessarily cause mass migration but are likely to alter human mobility from more voluntary toward more forced displacement or entrapment. A systems approach can be used as a starting point to address the urgent challenges of climate‐related human mobility. Key Points: In African drylands, migration is already being altered by changes in climate with uncertain outcomes under a 1.5° warming Impacts in climate‐sensitive sectors relying on migrants differ greatly, calling for an advancement of available evidence on regional scale A systems approach can address the urgent policy challenges regarding climate‐induced human mobility